The utility of measles and rubella IgM serology in an elimination setting, Ontario, Canada, 2009–2014 - Bolotin, Shelly (PLoS One, 2017)
In Canada, measles was eliminated in 1998 and rubella in 2000. Effective measles and rubella surveillance is vital in elimination settings, hinging on reliable laboratory methods. However, low-prevalence settings affect the predictive value of laboratory tests. We conducted an analysis to determine the performance of measles and rubella IgM testing in a jurisdiction where both infections are eliminated. 21,299 test results were extracted from the Public Health Ontario Laboratories database and 1,239 reports were extracted from the Ontario Integrated Public Health Information System (iPHIS) from 2008 and 2010 for measles and rubella, respectively, to 2014. Deterministic linkage resulted in 658 linked measles records (2009–2014) and 189 linked rubella records (2010–2014). Sixty-six iPHIS measles entries were classified as confirmed cases, of which 53 linked to laboratory data. Five iPHIS rubella entries were classified as confirmed, all linked to IgM results. The positive predictive value was 17.4% for measles and 3.6% for rubella. Sensitivity was 79.2% for measles and 100.0% for rubella. Specificity was 65.7% for measles and 25.8% for rubella. Our study confirms that a positive IgM alone does not confirm a measles case in elimination settings. This has important implications for countries that are working towards measles and rubella elimination.